An Optimal Control Analysis of Dengue Fever - Ilmayasinta, Nur; Febriyanti, Rahma; Prafianti, Rayinda Aseti; Zakiyah, Nabila Syarifah (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2023)
AbstractDengue fever is one of the most infectious diseases in the world, according to data issued by the World Health Organization in 2014. It is responsible for a huge number of deaths each year around the world, particularly in tropical nations. The dengue virus (DENV) causes dengue fever, which is spread by the female Aedes aegypti mosquito. We provide a mathematical model of dengue fever transmission through hospitalization with optimal management in this paper. Before being simulated in MATLAB, this optimum control problem is numerically resolved. Vaccination, pesticide use, and prevention are all examples of optimal control in this study. The simulation results demonstrate that dengue infection can be considerably reduced by vaccination, pesticide use, and prevention.Keywords: Dengue fever; Mathematical modelling; Optimal control. AbstrakDemam berdarah adalah salah satu penyakit paling menular di dunia, menurut data yang dikeluarkan oleh Organisasi Kesehatan Dunia pada tahun 2014. Penyakit ini menyebabkan banyak kematian setiap tahun di seluruh dunia, terutama di negara-negara tropis. Virus dengue (DENV) menyebabkan demam berdarah, yang disebarkan oleh nyamuk Aedes aegypti betina. Kami menyediakan model matematis penularan demam berdarah melalui rawat inap dengan penatalaksanaan optimal dalam makalah ini. Masalah kontrol optimal ini diselesaikan secara numerik sebelum disimulasikan di MATLAB. Vaksinasi, penggunaan pestisida, dan pencegahan merupakan contoh pengendalian yang optimal dalam penelitian ini. Hasil simulasi menunjukkan bahwa infeksi dengue dapat dikurangi dengan vaksinasi, penggunaan pestisida, dan pencegahan.Kata Kunci: Demam berdarah; Pemodelan matematika; Kontrol optimal. 2020MSC: 00A71, 92B05.